2002
DOI: 10.1021/ja0282240
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic Defect Centers at the MgO Surface. An Alternative Model to Oxygen Vacancies

Abstract: On the basis of embedded cluster calculations, we propose a new model for the structure of paramagnetic color centers at the MgO surface usually denoted as F(S)(H)(+) (an electron trapped near an adsorbed proton). These centers are produced by exposing the surface of polycrystalline MgO to H(2) followed by UV irradiation. We demonstrate that properties of H atom absorbed at surface sites such as step edges (MgO(step)) and reverse corner sites (MgO(RC)), formed at the intersection of two step edges, are compati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
199
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 133 publications
(211 citation statements)
references
References 60 publications
11
199
1
Order By: Relevance
“…The reaction is exothermic, and the computed value for DE (À0.66 eV) is close to that measured using microcalorimetry (À0.5 eV). [16] The MgÀH stretching frequency is found at ñ = 1446 cm À1 and a bending motion at ñ = 852 cm À1 ; both values are typical for hydride species. [18] The OÀH group vibrates at ñ = 3624 cm À1 .…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…The reaction is exothermic, and the computed value for DE (À0.66 eV) is close to that measured using microcalorimetry (À0.5 eV). [16] The MgÀH stretching frequency is found at ñ = 1446 cm À1 and a bending motion at ñ = 852 cm À1 ; both values are typical for hydride species. [18] The OÀH group vibrates at ñ = 3624 cm À1 .…”
Section: Methodsmentioning
confidence: 95%
“…This model suffers from several drawbacks, such as the high formation energy of the oxygen vacancy and the need to compensate negative charge to maintain electroneutrality. In recent years several alternative models have been proposed, which range from low-coordinated vacancies at steps and corners, [14] to neutral divacancies, [15] or morphological defects, [16] all of which involve an array of cations that act as an electron trap. However, recent theoretical calculations [17] surprisingly predicted that single low-coordinate cations on MgO can act as potential electron-trapping sites.…”
mentioning
confidence: 99%
“…At a closer look, the picture is more nuanced as it depends on the character and concentration of electron trapping sites in a particular system. For example, atomic hydrogen does not react with terraces at the MgO (001) surface, but donates electrons to three-coordinated Mg sites at corners and kinks at that surface, creating new [Mg + − O-H]-type centers [35,36]. The recent study of amorphous silica has concluded that, unlike in α quartz, atomic H can break some strained Si-O bonds and form a new thermodynamically stable defect, termed hydroxyl E center [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…For the sake of completeness we will also consider the behavior of hydrogen atoms adsorbed on the same surface because hydrogen may be regarded as the "first alkali metal". [6] The behavior of both alkali metal atoms [2][3][4][5]7] and hydrogen [8][9][10][11][12][13][14] adsorbed on MgO has been investigated previously, but a direct comparison has never been made. In addition, a comprehensive picture is often hampered by the complex morphology of the polycrystalline MgO surface used.…”
Section: Introductionmentioning
confidence: 99%
“…[15] The behavior of atomic hydrogen is very different and has been discussed in detail in a series of papers. [8][9][10][11][12][13][14] Herein, some account of the reactivity of hydrogen atoms is given, which will be restricted to the factors that distinguish them from the Group Ia metals. Finally, the trends in the chemical bonding and EPR properties of the alkali metal atoms going from the lighter (lithium) to the heavier (cesium) atoms are discussed.…”
Section: Introductionmentioning
confidence: 99%